Advanced Computing and Communication Technologies Proceedings of the 11th ICACCT 2018 - Mandal, Jyotsna Kumar; Bhattacharyya, Dhananjay; Auluck, Nitin (Advances in Intelligent Systems and Computing, 2019)
The book includes papers on a wide range of emerging research topics spanning theory, systems and applications of computing and communication technologies viz. Nonlinear Dynamics in Cryptography, Discrete domain Swarm Robotics, Machine Learning, Facility Layout Problem, Crowdfunding Projects, Deep Learning, MHD Nanofluid Flow, Medical Diagnostics, Human Computer Interface, Social Networking, System Performance, Wireless Sensor Networks, Cognitive Radio Networks, Antenna Design etc.; presented at the 11th International Conference on Advanced Computing and Communications Technologies (11th ICACCT 2018) held on 17-18 February, 2018 at Asia Pacific Institute of Information Technology, Panipat, India.